The post office : a comparative social history of Britain and Singapore, 1840s to 1880s - Yeow, Jeremy Yong Qi (2017)
The Postal Reform initiated by Sir Rowland Hill in 1840 changed the pricing system for mails of the British Post Office and implemented the Penny Post. This new system was officially implemented in Singapore in 1854, a colony of the British Empire then. The narrative of the reformed Post Office in both countries has often focus on the economic success of the new system and the important individuals in the institution. This paper shifts away from this narrative by focusing on the social history of the reformed Post Office from 1840 to 1889, examining the significances and implications of the reformed Post Office on the people, and the responses of the people towards the reformed Post Office. This paper argues, firstly, that the reformed Post Office was more than just a change in the postal system which lowered the price of posting a letter; secondly, the perceptions and responses towards the institution differed. To the British, it altered the fabric of their society, empowered and liberated them; whilst, to the people in Singapore, it intruded their way of life and conformed them to the British rule.